ERP measures indicate both attention and working memory encoding decrements in aging - Finnigan, Simon; O'Connell, Redmond G.; Cummins, Tarrant D. R.; Broughton, Megan; Robertson, Ian H. (Psychophysiology, 2011)
We investigated age‐related attention and encoding deficits, and their possible interaction, by analyzing visual event‐related potentials from young and older adults during a modified Sternberg word recognition task. Young adults performed more accurately, albeit not significantly so. P1 latency was shorter in young adults and correlated negatively with task accuracy (with age partialed out). These data support proposals that P1 indexes attentional suppression, which is less efficient in older adults. N1 was larger in older adults but did not correlate with accuracy. Young adults had higher P2 amplitudes and P2 latency correlated with accuracy (age partialed), supporting the view that semantic operations during encoding are affected by aging. These data indicate that attention (P1) and encoding (P2) decrements may contribute to memory or related cognitive decrements in aging, and P1 and P2 latency measures from appropriate paradigms may be salient ERP markers of these decrements.